Fluorochloridone induces primary cultured Sertoli cells apoptosis: Involvement of ROS and intracellular calcium ions-mediated ERK1/2 activation. (March 2018) - Liu, Luqing; Chang, Xiuli; Zhang, Yubin; Wu, Chunhua; Li, Rui; Tang, Liming; Zhou, Zhijun
Abstract: Fluorochloridone (FLC) is a widely used pyrrolidone selective herbicide and reported to induce testis injuries in male rats, but the underlying mechanism is largely unknown. In the present study, primary-cultured Sertoli cells were exposed to FLC at the concentration of 0–10.00 μM to study the mechanism of FLC-induced apoptosis. The roles of ROS, intracellular calcium, endoplasmic reticulum (ER), and ERK1/2 were looked at with ROS scavenger N -acetyl-cysteine (NAC), intracellular calcium chelator BAPTA-AM, ER calcium depleting agent thapsigargin (TG), and ERK1/2 inhibitor U0126, respectively. FLC induced dose-dependent apoptosis increase as well as the elevation in levels of ROS, intracellular calcium, and ERK1/2 activation. FLC treatment led to constantly increasing apoptotic rates and ERK1/2 activation over time, while inversed-V shaped change tendencies of ROS and intracellular calcium levels were observed. FLC-induced ROS generation disrupted the intracellular calcium homeostasis by attacking the ER, and the elevated intracellular calcium levels resulted in ERK1/2 over-phosphorylation and consequently promoted Sertoli cell apoptosis. Taken together, ROS and intracellular calcium-mediated ERK1/2 activation led to FLC-induced Sertoli cell apoptosis. Graphical abstract: Highlights: ROS is the initial factor in fluorochloridone-induced Sertoli cell apoptosis. Intracellular calcium released from ER functions as an intermediate factor between ROS, ERK1/2 activation and apoptosis. The ERK1/2 pathway, one branch of the MAPK pathways, participates in Sertoli cell apoptosis induced by fluorochloridone.